Role of ENSO Conditions on Particulate Organic Matter Concentrations and Elemental Ratios in the Southern California Bight - Fagan, Adam J.; Moreno, Allison R.; Martiny, Adam C. (Frontiers in Marine Science, 2019)
El Niño Southern Oscillation (ENSO) influences multi-year variation in sea-surface temperature and the intensity of upwelling in many Pacific regions. However, it is currently unknown how El Niño conditions will affect the concentration and elemental ratios of particulate organic matter (POM). To test this, we have been quantifying POM weekly for six years (2012 to 2017) at the MICRO time-series station in the Southern California Bight. We found a strong influence of the 2015 El Niño on sea-surface temperature and phosphate concentration but to a lesser extent on nitrate availability. The 2015 El Niño also resulted in low POC and POP concentrations, whereas PON concentrations declined by 26% during the whole sampling period. The changes in POM concentrations led to high C:P and N:P ratios. Following the changes in PON, C:N continued to climb reaching 9.4 at the end of the sampling. We suggest that an Eastern Pacific- vs. a Central Pacific-type El Niño as well as a switch in the Pacific Decadal Oscillation phase influenced the local response in POM concentrations and ratios.